39.4k views
1 vote
I need help asap, please !

5+(−3)(6x−5) simplify this

User Enesn
by
5.5k points

1 Answer

5 votes

Answer:

The simplified expression is 5+(-3)(6x-5)=2(10-9x)

Explanation:

Given expression is 5+(-3)(6x-5)

To simplify the given expression :

5+(-3)(6x-5)=5+((-3)(6x)-(-3)(5)) ( using the distributive property multiply each term to the each term in the factor )

=5+(-18x+15)

=5-18x+15

=-18x+20 ( adding the like terms )

=20-18x (rewritting the expression )

=2(10-9x) ( taking common term 2 outside the factor )

Therefore the simplified expression is 5+(-3)(6x-5)=2(10-9x)